Proffering Connections: Psychologising Experience in Psychotherapy and Everyday Life - Ekberg, Stuart (Frontiers in Psychology, 2021)
Conversation analytic research has advanced understanding of the psychotherapeutic process by understanding how psychotherapy is organised over time in and through interaction between clients and therapists. This study progresses knowledge in this area by examining how psychological accounts of experience are progressively developed across a range of helping relationships. Data include: 1) approximately 30 hours of psychotherapy sessions involving trainee therapists; 2) approximately 15 hours of psychotherapy demonstration sessions involving expert therapists; and 3) approximately 30 hours of everyday conversations involving close friends or family members. This article reports and analysis of techniques that are used to bring together two experiences that were discussed separately, to proffer a candidate connection between them. This proffering of candidate connections was recurrently used in psychotherapy. If confirmed by a client, a proffered connection could be used to develop a psychological account of a client’s experiences, which could then warrant some psychological intervention. In contrast, the proffering of connections was observed in only one of the everyday conversations included in the current study, where it was used to develop psychological accounts of experience. This shows that although proffering candidate connections is an everyday interactional practice, it appears to be used with greater frequency in psychotherapy, to advance its specific institutional aims.